A quantitative, longitudinal analysis of the impact of mathematics support in an Irish university. (11th May 2018) - Jacob, Maria; Ní Fhloinn, Eabhnat
Abstract: Mathematics support has become embedded in a large number of higher education institutes in Ireland and UK in particular. Measuring the impact of such support is a challenging task, which can be attempted either qualitatively, through the use of surveys or focus groups, or quantitatively, looking at data such as number of visits and subsequent exam performance. Here, we consider a quantitative analysis of the impact of a mathematics support centre in an Irish university, based on data gathered over the past 12 years. A binary logistic regression was carried out which showed that, when prior mathematical achievement and module studied were kept constant, the odds of a student who attended mathematics support once passing their module were 1.63 times higher than for one who had never engaged with the service. The odds for those who attended 15 or more times were almost 14 times higher. This study also showed that there was a significant difference between those who never engaged with mathematics support and those who attended once, meaning that such cohorts should be considered differently, which has not traditionally been done in other studies conducted to this point.